2018
DOI: 10.1007/s10953-018-0807-z
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Temperature on Liquid–Liquid Equilibrium of Methanol + Toluene + Hexane Ternary Systems at Atmospheric Pressure

Abstract: Your article is protected by copyright and all rights are held exclusively by Springer Science+Business Media, LLC, part of Springer Nature. This e-offprint is for personal use only and shall not be self-archived in electronic repositories. If you wish to selfarchive your article, please use the accepted manuscript version for posting on your own website. You may further deposit the accepted manuscript version in any repository, provided it is only made publicly available 12 months after official publication o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…In particular, by using a spectral clustering algorithm, we found that the distribution of the cluster sizes has a peculiar behavior in the critical region in that it shows both a “fat tail” corresponding to large aggregates and a non-negligible population of monomers. Accordingly, the Shannon entropy of this distribution calculated as a function of temperature possesses a maximum close to the experimental critical temperature, indicating accurate prediction of the phase transition …”
Section: Introductionmentioning
confidence: 61%
See 1 more Smart Citation
“…In particular, by using a spectral clustering algorithm, we found that the distribution of the cluster sizes has a peculiar behavior in the critical region in that it shows both a “fat tail” corresponding to large aggregates and a non-negligible population of monomers. Accordingly, the Shannon entropy of this distribution calculated as a function of temperature possesses a maximum close to the experimental critical temperature, indicating accurate prediction of the phase transition …”
Section: Introductionmentioning
confidence: 61%
“…Accordingly, the Shannon entropy of this distribution calculated as a function of temperature possesses a maximum close to the experimental critical temperature, indicating accurate prediction of the phase transition. 41 ■ METHODS Molecular Dynamics Simulation. Molecular dynamics (MD) simulations were carried out on two systems of methanol/hexane and Lennard−Jones (LJ) mixtures using the LAMMPS package.…”
Section: ■ Introductionmentioning
confidence: 99%